Social Media and Information Integrity in Elections in Nepal - Guragain, Yuba Raj (Global Focus, 2024)
This paper intends to explore how elections are being influenced through social media and what managerial measures have been adopted to promote information integrity in the electoral context of Nepal. Based on the synchronic approach under the information ecology framework of analysis with the data relating to 2022 local, provincial and federal elections in Nepal, this paper found that the political parties along with candidates and the Election Commission of Nepal enhanced the use of social media for disseminating electoral information in the elections. With the increase in the use of social media in elections, the coverage of the information environment has significantly expanded from political parties and individuals in the domestic setting to social media companies in the international setting. Moreover, besides the informational aspect of the social media in elections such as discussions, deliberations as well as concerns over disinformation and misinformation in elections, the aspects of emotional appeal and response are also found dominant. In this context, for promoting information integrity and deterring information pollution in elections, the Election Commission of Nepal as an independent election management body is found to have used a 3-P strategic model composed of promotional, preventive and punitive approaches with having a focus on informational aspect of social media in elections. However, depending on the deep-rooted social and cultural values, prevalent information culture, information behavior, globalized information environment as well as subject to the level of individual educational status and media literacy in the populace, myriad challenges including informational and emotional deceptions tend to appear in elections in Nepal.